(untitled) (Perner’s Contacts, 2012)
The content of the article is a quality comparison of two optical flow estimation methods. The comparison was always performed after a modification of the optical flow by thresholding and consequently after the morphological operation. The criterion MSE was chosen for the result quality check and the tool Matlab was used.